Number 8 (April 1979) - Southern Fishes Council (Southeastern Fishes Council Proceedings, 1979)
Distributional Notes on Fishes from Northern Georgia with Comments on the Status of Rare Species. By R.T. Bryant, et al., 4 pp.
Keywords: fishes; northern georgia